PELATIHAN LITERASI MEMBACA DAN MENULIS KREATIF MODEL JURNALISTIK DI MAN 1 MEDAN - Muhammad Lutfhi; Muya Syaroh Iwanda Lubis (MAJU : Indonesian Journal of Community Empowerment, 2026)
The phenomenon of motorcycle gangs and disrespectful acts among teenagers is one of the social issues that can interfere with the growth of character, security, and the future of young people. Teenagers are an age group who are looking for identity and are easily affected by a bad environment, such as joining a motorcycle gang, using social media incorrectly, fighting, being insulted, and doing actions that are not in accordance with good values. Therefore, it is necessary to make prevention efforts by providing socialization that can increase awareness and understanding of adolescents about the adverse effects of these behaviors. Socialization activities conducted to the students of in  Medan aims to provide an understanding of the dangers of motorcycle gangs and juvenile delinquency. This activity also aims to instill the value of discipline, responsibility, and form positive characters for students. Activities are carried out by providing material, actively discussing, watching explanatory videos, and conducting question and answer sessions. The material covered includes understanding and various types of juvenile delinquency, the causes that make teenagers involved in motorcycle gangs, legal and social impacts that occur, as well as ways to build good and beneficial relationships. The results showed an increase in participants ' understanding of the risks and consequences of involvement in motorcycle gangs and juvenile delinquent behavior. In addition, participants showed a more positive attitude towards the importance of maintaining relationships, obeying social norms, and developing their potential through useful activities. This activity is expected to be one of the preventive measures in forming a young generation with character, achievement, and free from negative environmental influences